Effects of aerobiosis and nitrogen source on the proton motive force in growing Escherichia coli and Klebsiella pneumoniae cells. - Kashket, E R (1981)
The electrochemical gradient of hydrogen ions, or proton motive force (PMF), was measured in growing Escherichia coli and Klebsiella pneumoniae in batch culture. The electrical component of the PMF (delta psi) and the chemical component (delta pH) were calculated from the cellular accumulation of radiolabeled tetraphenylphosphonium, thiocyanate, and benzoate ions. In both species, the PMF was constant during exponential phase and decreased as the cells entered stationary phase. Altering the growth rate with different energy substrates had no effect on the PMF. The delta pH (alkaline inside) varied with the pH of the culture medium, resulting in a constant internal pH. During aerobic growth in media at pH 6 to 7, the delta psi was constant at 160 mV (negative inside). The PMF, therefore, was 255 mV in cells growing at pH 6.3, and decreased progressively to 210 mV in pH 7.1 cultures. K. pneumoniae cells and two E. coli strains (K-12 and ML), including a mutant deficient in the H+-translocating ATPase and a pleiotropically energy-uncoupled mutant with a normal ATPase, had the same PMF during aerobic exponential phase. During anaerobic growth, however, both species had delta psi values equal to 0. Therefore, the PMF in anaerobic cells consisted only of the delta pH component, which was 75 mV or less in cells growing at pH 6.2 or greater. These data thus met the expectation that cells deriving metabolic energy from respiration have a PMF above a threshold value of about 200 mV when the ATPase functions in the direction of H+ influx and ATP synthesis; in fermenting cells, a PMF below a threshold value was expected since the enzyme functions in the direction of H+ extrusion and ATP hydrolysis. K. pneumoniae cells growing anaerobically had no delta psi whether the N source added was N2, NH+4 or one of several amino acids; the delta pH was unaffected. Therefore, any energy cost incurred by the process of nitrogen fixation could not be detected as an alteration of the proton gradient.